Pengaruh Pemahaman Kode Etik Auditor Pemerintah terhadap Kemampuan Auditor dalam Mendeteksi Kecurangan - Pratiwi Febri Ayu Wibowo; Yefta Andi Kus Noegroho (Jurnal Bisnis dan Ekonomi, 2020)
Government auditor has to realize the code of Ethics which is applicable to increase ability of fraudulence detection. This research is done with purpose to find out its roles in supports the auditor. The kind of research that has been used is quantitative descriptive with questionnaire data accumulation. The respondent is auditors that work in BPKP Central Java Delegation and Inspectorate in Central Java area. The result of the research show that code of Ethics comprehension by Government Auditor effects with their capability to detect the deception.